H HUBUNGAN KARAKTERISTIK DENGAN KEPATUHAN PERAWAT DALAM PELAKSANAAN TRIAGE COVID DI IGD - Hanura Aprilia (LPPM Universitas Sari Mulia, 2022)
Background: Triage of patients with Covid-19 is a new thing for nurses who work in the Emergency Department. The implementation of this triage must be carried out in accordance with the guidelines or procedures that have been set, but there are nurses who have not complied with it. This non-compliance varies based on the characteristics of nurses, namely age, gender, education level and length of work of nurses. Objective: This study aims to determine the relationship between age, gender, level of education, length of work and nurse compliance in the implementation of triage for Covid 19 patients in the ER Banjarmasin Islamic Hospital. Method: This study used a cross sectional design. The population was all nurses who served in the ER taken with a total population technique of 33 people. Data analysis using Spearman Rank. Result: The results of the study found that there was a relationship between age and nurse compliance in the implementation of triage for Covid 19 patients with a value of = 0.004 and the strength of the relationship was moderate (r = 0.492), there was a relationship between gender and nurse compliance with a value of = 0.000 and the strength of a strong relationship (r = 0.686), there is a relationship between the level of education and nurse compliance with a value of = 0.036 and the strength of the relationship is moderate (r = 0.367) and there is a relationship between length of work and nurse compliance with a value of = 0.001 and the strength of a strong relationship (r = 0.563). Conclusion: Nurses who have not complied should be given training or socialization about COVID-19 triage.